Ответы и объяснения

2013-05-20T15:26:27+04:00
2H3PO4 + 3CaCl2 = Са3(РО4)2 + 6HСl
2HCl+Na2SO4=H2SO4+2NaCl FeCl3+3AgNO3 = Fe(NO3)3+3AgCl KNO3+NaCl=NaNO3+KCl д) перечеркни. реакция не идет 6KOH + Al2(SO4)3 = 2Al(OH)3↓ + 3K2SO4
Лучший Ответ!
2013-05-20T15:45:22+04:00

2H3PO4 + 3CaCl2 = Ca3(PO4)2 + 6HCl

6H(+) + 2PO4(-3) + 3Ca(+2) + 6Cl(-) = Ca3(PO4)2↓ + 6H(+) + 6Cl(-)

2PO4(-3) + 3Ca(+2)  = Ca3(PO4)2↓

 

FeCl3 + 3AgNO3 = Fe(NO3)3 + 3AgCl

Fe(+3) + 3Cl(-) + 3Ag(+) + 3NO3(-) = Fe(+3) + 3NO3(-) + 3AgCl↓

3Cl(-) + 3Ag(+)  = 3AgCl↓

 

2NaOH + FeS = Fe(OH)2↓ + Na2S

2Na(+) + 2OH(-) + Fe(+2) + S(-2) = Fe(OH)2↓ + 2Na(+) + S(-2)

2OH(-) + Fe(+2)  = Fe(OH)2↓ 

 

6KOH + Al2(SO4)3 = 2Al(OH)3↓ + 3K2SO4

6K(+) + 6OH(-) + 2Al(+3) + 3SO4(-2) = 2Al(OH)3↓ + 6K(+) + 3SO4(-2)

6OH(-) + 2Al(+3) = 2Al(OH)3↓